The effect of gamma irradiation to eliminate fungal contamination on two model colors of Iranian paintings. (December 2021) - Sheikh, N.; Babrud, R. Betesho; Khatamifar, F.
Abstract: Improper storage conditions may cause fungal contamination of old paintings. In this regard, gamma radiation which is an effective method for fungal decontamination of objects can be applied. However, the side effect of this method, the change of colors due to gamma radiation, should be investigated. In this study, to define the dose of decontamination, painted canvases with mixtures of two mineral pigments and binder were prepared and used as model samples. These model samples were aged and then inoculated with spores of two common types of fungal strains, Penicillium chrysogenum, and Aspergillus niger . The fungal radiation sensitivity ( D 10 value) on the samples was determined. The minimum sterilization dose of gamma-ray ( D m ) for decontamination was calculated according to the D 10 values, and 3 logarithmic cycles reduction of initial contamination. Results showed that D 10 values of Penicillium chrysogenum ATCC 12690 and Aspergillus niger CBS 104.57 spores on model samples were 1.47 ± 0.3 and 0.702 ± 0.13 kGy respectively. Sterility test presented D m of 5 kGy as sufficient dose to achieve 3 logarithmic cycles reduction of initial contamination. Also, in this study, the changes of the model colors due to the irradiation process were evaluated by using the colorimetric method. For this purpose, after the aging of model colors, the aged samples were irradiated at a dose of 5 kGy ( D m ). Colorimetric results for fresh, aged, aged & irradiated model colors were obtained and revealed that the irradiation process with a dose of 5 kGy did not induce any significant color alterations. Highlights: Painted canvases with mixtures of pigment and binder were used as model samples. The model samples were aged & inoculated with spores of two types of fungal strains. Sterility test on inoculated model samples presented D m of 5 kGy. It was seen that the aging process can sometimes affect colors. Radiation treatment impact on color changes of the model colors was insignificant.